2022
DOI: 10.21203/rs.3.rs-2133456/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The overexpression and clinical significance of TBX15 in human gliomas

Abstract: T-box transcription factor 15 (TBX15) is upregulated in a variety of tumors and has been reported to promote uncontrolled proliferation of tumor cells and induce tumor cells to avoid apoptosis, thus accelerating the malignant transformation of malignant tumors. However, the prognostic value of TBX15 in glioma and its relationship with immune infiltration remain unknown. In this study, we intended to explore the prognostic value of TBX15 and its link to glioma immune infiltration and examine TBX15 expression in… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…These variances in age groups and tumor types inherently introduce biases, making direct comparisons challenging. Moreover, another study (published in Chinese) by Yan et al found that BDNF expression was greatly upregulated in human glioma tissue [20]. However, they tested gliomas of different WHO grades.…”
Section: Discussionmentioning
confidence: 99%
“…These variances in age groups and tumor types inherently introduce biases, making direct comparisons challenging. Moreover, another study (published in Chinese) by Yan et al found that BDNF expression was greatly upregulated in human glioma tissue [20]. However, they tested gliomas of different WHO grades.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we also noted that these genes also showed high expression in other tumor tissues, such as colorectal and pancreatic (not shown). Some hub genes (TBX15 and VCAN) are not well known, but have been reported to be highly expressed in many tumors in recent years, such as gliomas [36], ovarian cancer [37].…”
Section: Comparison Of Hub Genes Expressions Between Normal and Tumor...mentioning
confidence: 99%